ASSESSING BULAKBARU'S ABRASSION VULNERABILITY THROUGH MANGROVE DENSITY ANALYSIS USING REMOTE SENSING AND GIS - Husna, Vina Nurul; Jamhur, Jamhur; Setyaningsih, Wahyu; Wicaksana, Muhammad Guruh Bintang; Nabila, Erva Destianti; Nadhiroh, Ria Kholifatun (Universitas Negeri Makassar, 2025)
Indonesian mangroves have faced serious damage over the past 30 years, losing a significant portion (22.6%) of the global total. This loss harms communities, like the one in Bulakbaru village, Jepara, where coastal erosion (abrasion) is a major problem. From 1995 to 2019, Jepara's coast lost over half (55%) of its mangrove cover. The study area in Bulakbaru shows a worrying trend: increasing abrasion, a lack of awareness among residents about the issue, and no preventative measures to stop further erosion. This research used remote sensing data to analyze the vulnerability of Bulakbaru Beach to abrasion. By combining nine different factors, researchers created a map showing areas more or less susceptible to erosion. Areas with denser mangroves fell into the low vulnerability category, while those with less mangrove cover were classified as medium vulnerability. Field observations confirmed these results - denser mangroves offered better protection. Unfortunately, most of Bulakbaru's mangroves, especially those closest to the sea, are damaged. This damage is caused by pollution (garbage) hindering their growth and strong waves breaking them.The study suggests solutions to reduce abrasion vulnerability: restoring the mangroves and implementing Wave Breaking Equipment (APO) to create a more favorable environment for mangrove growth.